2018
DOI: 10.1002/masy.201800078
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polystyrene (PS)/Modified Ni‐Al LDH Nanocomposite: Role of Composition, Modifier and Synthesis Route of Layered Double Hydroxides (LDH)

Abstract: Layered double hydroxides (LDH) are two‐dimensional nanostructured materials, which impart flame retardancy property and improvement in various properties on incorporation into the polymer matrix. In this study, Ni‐Al LDH with a molar ratio of 2:1 and 3:1 (2NiAl and 3NiAl) was prepared by co‐precipitation method and Ni‐Al LDH with a molar ratio of 2:1 (NiAl urea) was also synthesized by the urea hydrolysis method. As the d‐spacing of these as‐synthesized LDHs is very small (≈0.8 nm) as well as hydrophilic in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Designing and regulating the interlayer spacing structure has become an essential topic in the research of LDH materials. Fruitful results have been achieved using experimental methods to modulate the interlayer spacing, such as changing the interlayer spacing and structural stability by adjusting the anion size and type and regulating the basal layer metal element ratio and synthesis conditions to improve functional properties. NiAl-LDHs have many research reports on electricity storage, catalysis, adsorption, etc., and are expected to achieve industrial application. The effects of anion intercalation of CO 3 2– , NO 3 – , Cl – , sodium dodecyl sulfate, etc., on the interlayer spacing of NiAl-LDHs have all shown that large interlayer spacing has a positive effect on supercapacitor and catalytic performances. However, the microscopic mechanisms affecting the layer spacing and stability of NiAl-LDHs were not systematically reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Designing and regulating the interlayer spacing structure has become an essential topic in the research of LDH materials. Fruitful results have been achieved using experimental methods to modulate the interlayer spacing, such as changing the interlayer spacing and structural stability by adjusting the anion size and type and regulating the basal layer metal element ratio and synthesis conditions to improve functional properties. NiAl-LDHs have many research reports on electricity storage, catalysis, adsorption, etc., and are expected to achieve industrial application. The effects of anion intercalation of CO 3 2– , NO 3 – , Cl – , sodium dodecyl sulfate, etc., on the interlayer spacing of NiAl-LDHs have all shown that large interlayer spacing has a positive effect on supercapacitor and catalytic performances. However, the microscopic mechanisms affecting the layer spacing and stability of NiAl-LDHs were not systematically reported.…”
Section: Introductionmentioning
confidence: 99%
“… 17 19 NiAl-LDHs have many research reports on electricity storage, catalysis, adsorption, etc., and are expected to achieve industrial application. 20 22 The effects of anion intercalation of CO 3 2– , NO 3 – , 23 Cl – , 24 sodium dodecyl sulfate, 25 etc., on the interlayer spacing of NiAl-LDHs have all shown that large interlayer spacing has a positive effect on supercapacitor and catalytic performances. However, the microscopic mechanisms affecting the layer spacing and stability of NiAl-LDHs were not systematically reported.…”
Section: Introductionmentioning
confidence: 99%